2019
DOI: 10.1002/asia.201901311
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design Strategy of Thermally Activated Delayed Fluorescent Emitters Using CN‐Substituted Imidazopyrazine as a New Electron‐Accepting Unit

Abstract: Thermally activated delayed fluorescence( TADF)based organic light-emitting diodes (OLEDs) have attracted enormous attention recently due to their capabilityt or eplace conventionalp hosphorescent organic light-emitting diodes for practical applications.I nt his work, an ewly designed CN-substituted imidazopyrazine moiety was utilized as an electron-accepting unit in aT ADF emitter.T wo TADF emitters, 8-(3-cyano-4-(9,9-dimethylacridin-10(9H)-yl)phenyl)-2-phenylimidazo[1,2-a]pyrazine-3-carbonitrile (Ac-CNImPyr)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Organic-emitter-based thermally activated delayed fluorescent (TADF)-OLEDs are considered competent alternatives to Ph-OLEDs, as internal quantum efficiencies of up to 100% are achievable in both cases. [7][8][9][10][11][12][13] Compared to precious-metalbased phosphorescent emitters, TADF emitters are inexpensive and allow for greater diversity in their design. Organic materials with a small singlet-triplet energy gap (DE ST ) are capable of converting non-radiative triplet excitons to radiative singlet excitons via a reverse intersystem crossing (RISC) process.…”
Section: Introductionmentioning
confidence: 99%
“…Organic-emitter-based thermally activated delayed fluorescent (TADF)-OLEDs are considered competent alternatives to Ph-OLEDs, as internal quantum efficiencies of up to 100% are achievable in both cases. [7][8][9][10][11][12][13] Compared to precious-metalbased phosphorescent emitters, TADF emitters are inexpensive and allow for greater diversity in their design. Organic materials with a small singlet-triplet energy gap (DE ST ) are capable of converting non-radiative triplet excitons to radiative singlet excitons via a reverse intersystem crossing (RISC) process.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In order to achieve efficient rISC and thus TADF, TADF emitters should be designed to possess small singlet-triplet splitting energy (DE ST ) between the singlet state (S 1 ) and the triplet state (T 1 ). [6][7][8] In this regard, many studies revealed that a donor-acceptor (D-A) design with a large twisting angle is the best universal strategy. Evidently, such a strategy can effectively separate the highest occupied molecular orbitals (HOMOs) and the lowest unoccupied molecular orbitals (LUMOs), and thus achieve the minimizing exchange integral and consequently a small DE ST .…”
Section: Introductionmentioning
confidence: 99%
“…The functionalization of the imidazole-containing domain with a strongly electron-withdrawing cyano-group and a reduced singlet-triplet energy gap, on the other hand, has received special attention as a universal and appealing strategy for creating AIE-active fluorophores, including those with thermally activated delayed fluorescence (TADF) [39]. For instance, the authors of [40] recently developed TADF materials with C3-functionalized cyano-group 2-phenylimidazopyrazine as an acceptor unit linked to either acridine or phenoxazine donor units, and for these fluorophores an EQE of about 12.7% was achieved. In addition, the use of 2-phenylimidazo[1,2-a]pyridine containing cyano-group as an acceptor has been reported as a tool for designing dark blue emitters with a relatively high fluorescence quantum yield [36,41].…”
Section: Introductionmentioning
confidence: 99%